Velocity‐specific and time‐dependent adaptations following a standardized Nordic Hamstring Exercise training. (10th April 2017) - Alt, T.; Nodler, Y. T.; Severin, J.; Knicker, A. J.; Strüder, H. K.
Abstract : The Nordic Hamstring Exercise (NHE) is effective for selective hamstring strengthening to improve muscle balance between knee flexors and extensors. The purpose of this study (within subject design of repeated measures) was to determine the effects of a standardized 4‐week NHE training on thigh strength and muscle balance with concomitant kinetic and kinematic monitoring. Sixteen male sprinters (22 years, 181 cm, 76 kg) performed a standardized 4‐week NHE training consisting of three sessions per week (each 3×3 repetitions). Six rope‐assisted and six unassisted sessions were performed targeting at a constant knee extension angular velocity of 15°/s across a 90‐100° knee joint range of motion. Kinetic (peak and mean moment, impulse) and kinematic parameters (eg, ROM to downward acceleration, ROMDWA ) were recorded during selected sessions. Unilateral isokinetic tests of concentric and eccentric knee flexors and extensors quantified muscle group‐, contraction mode‐, and velocity‐specific training adaptations. Peak moments and contractional work demonstrated strong interactions of time with muscle group, contraction modes, and angular velocities (η²>.150). NHE training increased eccentric hamstring strength by 6%‐14% as well as thigh muscle balance with biggest adaptations at 150°/s 2 weeks after NHE training. Throughout the training period significant increases ( P <.001) of peak (η²=.828) and mean moments (η²=.611) became apparent, whereas the impulse and the ROMDWA of unassisted NHE repetitions remained unchanged ( P >.05). A 4‐week NHE training significantly strengthened the hamstrings and improved muscle balance between knee flexors and extensors. Despite the slow training velocity, biggest adaptations emerged at the highest velocity 2 weeks after training ended.